Collaborative learning via CiA - collaborators in action - Balakrishnan, Vimala (2017)
The present study investigated the effect(s) of using a collaborative tool, aptly named Collaborators in Action (CiA) in improving students' collaborative learning. CiA was developed based on the Social Media Acceptance Model (SMAM), which consists of four main predictors, namely Communication Functionality (i.e. functions supporting communication process), Effort (i.e. ease of use), Performance (i.e. usefulness of CiA) and Self (i.e. skill set and enjoyment). CiA has several core components, such as Collaborative Activities that enable the lecturer to administer various collaborative tasks to the students, Tracking and Monitoring that allows the students' collaboration level to be monitored and Sentiment Analysis, which provides the general polarity of the students' sentiment for a particular topic or activity. The tool was built and customized for the Probability and Statistics, that is, a core course that require a certain number of collaborative tasks to be carried out. Both pre-test and post-test surveys were administered among 33 undergraduate students, with the students using CiA as part of their learning for the second half of the semester (i.e. approximately six weeks). The pre-test questionnaire was given to the students at the beginning of the experiment and they were asked to provide their opinions based on the current practice of learning. At the end of the sixth week, the posttest questionnaire was administered. Paired-sample t-test revealed the students to be more receptive in using CiA in collaborative learning. A further in-depth analysis of the survey instruments and CiA is yet to be carried out, and therefore more results will be provided at a later stage.